A polylactic acid composite material with a sandwich honeycomb structure and a preparation method thereof

By combining the Pickering emulsion template method and the melt blending method, a sandwich honeycomb structure of polylactic acid composite material was constructed, which solved the problem of poor dispersion of nanofillers, and achieved a polylactic acid composite material with high conductivity, high electromagnetic shielding and high thermal conductivity. Reduced production costs and expanded application areas.

CN116855047BActive Publication Date: 2025-02-07ZHEJIANG UNIV OF TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310757653.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-06-26
Publication Date
2025-02-07
Estimated Expiration
2043-06-26

AI Technical Summary

Technical Problem

The dispersion of nanofillers in polylactic acid nanocomposites is poor, resulting in reduced conductivity and increased production costs.

Method used

Using a combination of Pickering emulsion template method and traditional melt blending method, the carbon nanotubes are uniformly dispersed by adding cellulose nanofibers to the aqueous solution of carbon nanotubes, and then melt blending them with polylactic acid to form PLA /xCNT composite particles and expanded graphite is coated on the surface of the composite particles by mechanical blending, and heat-pressed to build a sandwich honeycomb structure.

Benefits of technology

It significantly improves the electrical, electromagnetic shielding and thermal conductivity of composite materials, reduces dispersant content, reduces production costs, and expands its application in electronic devices and communication equipment fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116855047B_ABST
    Figure CN116855047B_ABST
Patent Text Reader

Abstract

The invention discloses a polylactic acid composite material with a sandwich honeycomb structure and a preparation method thereof. The composite material includes polylactic acid, carbon nanotubes, cellulose nanofibers, and expanded graphite. The composite material is prepared by the following method: dispersing carbon nanotubes in an aqueous solution as a water phase under the action of a cellulose nanofiber dispersion, dissolving polylactic acid in dichloromethane as an oil phase, mixing the water phase and the oil phase, homogenizing and emulsifying to obtain a Pickering emulsion, and obtaining a PLA / CNT composite masterbatch after the solvent evaporates; melt blending the PLA / CNT composite masterbatch with polylactic acid, crushing and collecting PLA / xCNT composite particles; blending the PLA / xCNT composite particles with expanded graphite and hot pressing to obtain a polylactic acid composite material PLA / xCNT@EG with a sandwich honeycomb structure. The composite material PLA / xCNT@EG exhibits high electrical conductivity, high electromagnetic shielding and high thermal conductivity, which is conducive to expanding its application in the fields of electronic devices, communication equipment, etc.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of polymer material manufacturing, and in particular relates to a multifunctional composite material. Background Art

[0002] The rapid development of wireless communication technology and portable smart electronic devices has brought many conveniences to people's daily lives. But it is worth noting that the use of these high-frequency and high-power electronic devices has also made electromagnetic wave pollution a common problem in people's daily lives. These electromagnetic waves will not only damage sensitive electronic equipment and systems, but also cause great harm to people's bodies. However, ideal electromagnetic shielding materials will convert electromagnetic energy into heat, which will undoubtedly aggravate the local heat accumulation of electronic devices. These local heat accumulations will seriously affect the working efficiency and service life of the equipment. Therefore, how to effectively solve the problem of harmful electromagnetic waves while maximizing the thermal conductivity of materials closely related to heat dissipation, so as to develop new multifunctional materials with high thermal conductivity and high electromagnetic shielding performance, is of great significance.

[0003] Although traditional metal materials are widely used in industry due to their good electrical conductivity, electromagnetic shielding and thermal conductivity, their high density, difficult processing and poor corrosion resistance limit their application in a wider range of fields. Polymer-based composites are considered to be one of the most important materials in the next generation of electronic devices due to their advantages such as light weight, easy processing and low cost. In addition, due to the increasingly severe environmental pollution problem, biodegradable polymer materials have been increasingly widely used in various fields due to their environmental friendliness, and the use of biodegradable polymer materials to replace traditional petroleum-based polymer materials has become an inevitable trend. Polylactic acid (PLA), as one of the most important biodegradable polymers, has the advantages of rigidity, biodegradability and transparency. However, the inherent functionality of PLA is poor and is far from meeting the requirements of practical applications. Introducing nanofillers into the PLA matrix has been considered to be an effective strategy to improve the electrical conductivity, thermal conductivity and electromagnetic shielding properties of PLA nanocomposites. However, the key is to construct a nanofiller network structure in the composite material to provide a transmission path for electrons and phonons and at the same time better absorb and reflect electromagnetic waves, thereby realizing the multifunctionality of PLA nanocomposites. So far, researchers have used many different methods to construct efficient nanofiller networks in polylactic acid matrices, such as freeze-drying to construct a nanofiller skeleton with a porous structure, then impregnating the polymer into the pores, and constructing a layered structure of nanofillers and polymers through vacuum ultrasonic-assisted self-assembly technology. In addition, another important issue that limits the multifunctionalization of composite materials is the poor dispersibility of nanofillers, which is easy to agglomerate in the matrix, seriously affecting the conductive properties of the composite materials, and thus having a negative impact on the multifunctionalization of the composite materials. The Pickering emulsion blending method has been successfully used to prepare polymer-based nanocomposites with good dispersibility. However, the prepared Pickering emulsion often requires a higher content of dispersant to promote the dispersion of carbon nanotubes (CNTs), which also hinders the formation of a continuous conductive network of carbon nanotubes, resulting in reduced conductive properties of the composite materials and increased production costs. Summary of the invention

[0004] In view of the problems in the prior art that the nanofiller in the polylactic acid nanocomposite material has poor dispersibility, high dispersant content leads to reduced electrical conductivity and increased production costs, the present invention provides a polylactic acid composite material with a sandwich honeycomb structure and a preparation method thereof. The preparation method of the present invention is simple, easy to operate, and has high process stability. The prepared composite material has excellent electrical conductivity, electromagnetic shielding and thermal conductivity, and has extremely high practical value in multifunctional applications.

[0005] In the first aspect of the present invention, a PLA / CNT@EG composite material with a sandwich honeycomb structure is provided. The composite material includes a matrix and a filler. The matrix is ​​PLA, and the filler includes carbon nanotubes CNT, cellulose nanofibers CNF, and expanded graphite EG. The composite material is prepared by the following method: dispersing carbon nanotubes in an aqueous solution as an aqueous phase under the action of a cellulose nanofiber dispersion, dissolving polylactic acid in dichloromethane as an oil phase, mixing the aqueous phase and the oil phase, homogenizing and emulsifying to obtain a Pickering emulsion, and obtaining a PLA / CNT composite masterbatch after the solvent evaporates; melt blending the PLA / CNT composite masterbatch with polylactic acid, crushing and collecting to obtain PLA / xCNT composite particles; blending the PLA / xCNT composite particles with expanded graphite and hot pressing to obtain a PLA / xCNT@EG composite material with a sandwich honeycomb structure. The composite material PLA / xCNT@EG exhibits high electrical conductivity, high electromagnetic shielding and high thermal conductivity, which is conducive to expanding its application in the fields of electronic devices, communication equipment, etc. In the PLA / xCNT composite particles, x means that the PLA / xCNT composite particles include x wt % of carbon nanotubes.

[0006] Specifically, the composite material includes 64.87-88.04 wt% of polylactic acid, 0.86-2.32 wt% of cellulose nanofibers, 1.72-4.64 wt% of carbon nanotubes, and 5-30 wt% of expanded graphite.

[0007] In the PLA / CNT composite masterbatch, the mass ratio of carbon nanotubes to polylactic acid is preferably 0.08 to 0.1:1, more preferably 0.1:1.

[0008] Specifically, the PLA / xCNT composite particles include 2.5-5wt% carbon nanotubes; preferably, the PLA / xCNT composite particles include 5wt% carbon nanotubes, that is, the PLA / xCNT composite particles are preferably PLA / 5CNT composite particles. The method for preparing PLA / xCNT composite particles by combining the Pickering emulsion template method and the traditional melt blending method enables the carbon nanotubes to be dispersed secondary in the polylactic acid matrix, which not only reduces the content of the dispersant, but also solves the problem of easy agglomeration in the matrix due to poor dispersion of the nanofiller, and promotes the formation of a continuous conductive network of carbon nanotubes. PLA / xCNT composite particles, as the sandwich core of the composite material PLA / CNT@EG, are of great significance to improving the thermal conductivity of the composite material PLA / CNT@EG.

[0009] Specifically, the particle size of the PLA / xCNT composite particles is 50-900 μm; preferably, the particle size of the PLA / xCNT composite particles is 200-500 μm. The particle size of the PLA / xCNT composite particles as the sandwich core has an important influence on the conductive properties of the composite material.

[0010] Specifically, the composite material PLA / xCNT@EG includes 70-95wt% PLA / xCNT composite particles; preferably, the composite material PLA / xCNT@EG includes 70-95wt% PLA / 5CNT composite particles; more preferably, the composite material PLA / xCNT@EG includes 70-90wt% PLA / 5CNT composite particles. Expanded graphite is coated on the surface of PLA / 5CNT composite particles by mechanical blending, and an enhanced sandwich honeycomb structure is formed by hot pressing, so that the thermal conductivity of the PLA / 5CNT@xEG composite material is greatly improved. At the same time, by optimizing the ratio of PLA / xCNT composite particles to expanded graphite, the electrical conductivity, thermal conductivity and electromagnetic shielding performance of the composite material are further improved.

[0011] The second aspect of the present invention provides a method for preparing a polylactic acid composite material having a sandwich honeycomb structure, the preparation method being as follows:

[0012] Step 1: dispersing carbon nanotubes in an aqueous solution as a water phase under the action of a cellulose nanofiber dispersion, dissolving polylactic acid in dichloromethane as an oil phase, mixing the water phase and the oil phase, and homogenizing and emulsifying them to obtain a Pickering emulsion, and obtaining a PLA / CNT composite masterbatch after the solvent evaporates;

[0013] Step 2: melt-blending the PLA / CNT composite masterbatch with polylactic acid, crushing and collecting to obtain PLA / xCNT composite particles;

[0014] Step 3: The PLA / xCNT composite particles and expanded graphite are mixed and hot-pressed to obtain a polylactic acid composite material PLA / xCNT@EG with a sandwich honeycomb structure.

[0015] Specifically, in step 1, the solid content of the cellulose nanofiber dispersion is 2.5-3 wt %. Cellulose nanofibers have excellent mechanical properties and biodegradability and are an ideal dispersant.

[0016] Specifically, in step 1, the carbon nanotubes are uniformly dispersed in the aqueous solution after ultrasonication at a power of 540 to 600 W for 0.5 to 1 hour in an ultrasonic cell crusher under the action of the cellulose nanofiber dispersion. The ultrasonic method makes the carbon nanotubes more uniformly dispersed in the aqueous solution, which is beneficial to improve the stability of the Pickering emulsion in the subsequent steps and avoid agglomeration between the carbon nanotubes.

[0017] Specifically, in step 1, the mass ratio of carbon nanotubes to cellulose nanofibers is preferably 1 to 2:1.

[0018] Specifically, in step 1, the mass ratio of carbon nanotubes to polylactic acid is preferably 0.08 to 0.1:1, more preferably 0.1:1.

[0019] Specifically, in step 2, the PLA / CNT composite masterbatch and polylactic acid are melt-blended in a Haake torque rheometer at 180-190° C. and 50-60 r / min for 8-10 min.

[0020] Specifically, in step 2, the weight amount of PLA / CNT composite masterbatch and polylactic acid is preferably such that the content of carbon nanotubes in the PLA / xCNT composite particles is 2.5-5 wt %.

[0021] Specifically, in step 3, the mass amount of expanded graphite is such that the final content of the polylactic acid composite material PLA / xCNT@EG in the product is 5-30%. The expanded graphite is tightly coated on the middle and outer sides of the sandwich honeycomb structure by mechanical blending, which promotes the overlap between the one-dimensional carbon nanotubes and the two-dimensional expanded graphite.

[0022] Furthermore, the method for preparing the polylactic acid composite material having a sandwich honeycomb structure is preferably carried out according to the following steps:

[0023] Step 1: adding carbon nanotubes and cellulose nanofiber dispersion having a solid content of 2.5-3wt% to deionized water in a mass ratio of carbon nanotubes to cellulose nanofibers of 1-2:1, stirring for 0.5-1h, and then ultrasonicating in an ultrasonic cell crusher at a power of 540-600W for 0.5-1h to uniformly disperse the carbon nanotubes in the aqueous solution, which is used as the aqueous phase; then fully dissolving the polylactic acid powder in a dichloromethane solvent in a ratio of polylactic acid mass / dichloromethane volume of 1:8-12, and This is used as the oil phase; according to the volume ratio of the oil phase to the water phase of 1:2-4, the water phase of the carbon nanotubes / cellulose nanofibers is poured into the oil phase, the mixture is placed in a homogenizer and homogenized and emulsified at 10000-14000 rpm for 2-5 minutes to obtain a stable Pickering emulsion, and then the homogenized and emulsified Pickering emulsion is volatilized at room temperature for 24 hours to obtain a PLA / 10CNT composite masterbatch, wherein the PLA / 10CNT composite masterbatch includes 10% carbon nanotubes;

[0024] Step 2: melt-blending a PLA / 10CNT composite masterbatch with a mass ratio of 1:1 to 3 with polylactic acid powder in a Haake torque rheometer at 180 to 190°C and 50 to 60 r / min for 8 to 10 minutes, so that the carbon nanotube content in the PLA / 10CNT composite masterbatch is diluted to obtain a PLA / xCNT composite, wherein the PLA / xCNT composite particles include 2.5 to 5 wt% carbon nanotubes; finally, the PLA / xCNT composite is crushed in a high-speed crusher, and the PLA / xCNT composite particles with a particle size of 50 to 900 μm are sieved and collected;

[0025] Step 3: The PLA / xCNT composite particles and the expanded graphite with a final content of 5-30% are mechanically blended in a high-speed mixer at 20000r / min for 2min, so that the expanded graphite is coated on the surface of the PLA / xCNT composite particles and then hot-pressed in a flat vulcanizer to prepare a PLA / xCNT@xEG composite material with a reinforced sandwich honeycomb structure.

[0026] More preferably, the solid content of the cellulose nanofiber dispersion in step 1 is 2.5 wt %, and it is stirred in deionized water for 1 hour.

[0027] More preferably, the ultrasonic cell disruptor in step 1 is used for ultrasonication at a power of 600 W for 0.5 h.

[0028] More preferably, the mass ratio of carbon nanotubes to cellulose nanofibers in the aqueous phase in step 1 is 2:1.

[0029] More preferably, the ratio of the mass of polylactic acid to the volume of dichloromethane in the oil phase in step 1 is 1:10.

[0030] More preferably, the volume ratio of the water phase to the oil phase in step 1 is 1:3.

[0031] More preferably, the homogenizer in step 1 homogenizes and emulsifies at 12000 rpm for 3 min.

[0032] More preferably, the PLA / 10CNT composite masterbatch and the polylactic acid powder in step 2 are melt-blended in a Haake torque rheometer at 180° C. and 60 r / min for 8 min.

[0033] More preferably, in step 2, the PLA / xCNT composite is crushed in a high-speed crusher, and PLA / xCNT composite particles with a particle size of 200 to 500 μm are collected by sieving.

[0034] Compared with the prior art, the beneficial effect of the present invention is that the present invention provides a secondary dispersion method combining the Pickering emulsion template method and the traditional melt blending to improve the dispersion of carbon nanotubes in the polylactic acid matrix and construct a sandwich honeycomb filler network structure to prepare a high-conductivity, high-electromagnetic shielding, high-thermal conductivity polylactic acid / carbon nanotube / expanded graphite nanocomposite material. Among them, the present invention first adds cellulose nanofibers to the aqueous solution of carbon nanotubes to achieve uniform dispersion of carbon nanotubes in the aqueous phase, and then homogenizes and emulsifies the aqueous phase with the oil phase of the dichloromethane solution containing polylactic acid, stands for volatilization, and filters and dries to obtain a PLA / CNT composite masterbatch. The obtained PLA / CNT composite masterbatch is then melt blended with polylactic acid to obtain a well-dispersed PLA / xCNT composite. The composite was then crushed in a high-speed pulverizer to obtain the required PLA / xCNT composite particles. Finally, the PLA / xCNT composite particles were mechanically blended with expanded graphite with different final contents in a high-speed mixer to prepare a PLA / xCNT@EG composite material with a sandwich honeycomb structure.

[0035] The present invention improves the dispersion of filler carbon nanotubes in a polylactic acid matrix, thereby forming a more complete carbon nanotube network in the polylactic acid matrix. At the same time, the external tightly coated expanded graphite network in the sandwich honeycomb structure and the overlap between the one-dimensional carbon nanotubes and the two-dimensional expanded graphite make the composite material have a more complete and dense filler network, thereby achieving high electrical conductivity, high electromagnetic shielding and high thermal conductivity of the PLA / xCNT@EG composite material, which is conducive to expanding its application in electronic devices, communication equipment and other fields. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] Figure 1 It is a comparison chart of the electrical conductivity of the composite materials prepared in Examples 1-4 and Comparative Example 1.

[0037] Figure 2It is a comparison chart of the electromagnetic shielding performance of the composite materials prepared in Examples 1-4 and Comparative Example 1.

[0038] Figure 3 It is a comparison chart of the thermal conductivity of the composite materials prepared in Examples 1-4 and Comparative Example 1.

[0039] Figure 4 It is a comparison chart of the electrical conductivity of the composite materials prepared in Examples 1-4 and Comparative Examples 2-6.

[0040] Figure 5 It is a comparison chart of the electromagnetic shielding performance of the composite materials prepared in Examples 1-4 and Comparative Examples 2-6.

[0041] Figure 6 It is a comparison chart of the thermal conductivity of the composite materials prepared in Examples 1-4 and Comparative Examples 2-6.

[0042] Figure 7 It is a comparison chart of the electrical conductivity of the composite materials obtained in Example 4 and Comparative Examples 7-8.

[0043] Figure 8 It is a comparison chart of the electromagnetic shielding performance of the composite materials obtained in Example 4 and Comparative Examples 7-8.

[0044] Fig. 9 It is a comparison chart of the thermal conductivity of the composite materials obtained in Example 4 and Comparative Examples 7-8.

[0045] Fig.10 1 is a SEM image of the composite material prepared in Example 4 and Comparative Examples 7-8. DETAILED DESCRIPTION

[0046] The following is an explanation of the embodiments of the present invention by specific specific examples, and those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied by other different specific embodiments, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present invention. It should be noted that, in the absence of conflict, the features in the following embodiments and embodiments can be combined with each other. In the embodiments of the present invention, the methods used are all conventional methods unless otherwise specified, and the reagents used can be obtained from commercial sources.

[0047] The raw materials in the following examples are all commercially available materials:

[0048] The polylactic acid (PLA) is NatureWorks 4032D, with a density of 1.24 g / cm 3 , melting point 150~160℃, melt index 6.17g / 10min (210℃, 2.16kg), weight average molecular weight and number average molecular weight are 1.85×105 and 1.22×10 5 g / mol;

[0049] The cellulose nanofiber (CNF) is a cellulose nanofiber suspension with a solid content of 2.5 wt%, wherein the cellulose nanofiber has a length of 1 to 10 μm and a diameter of 20 to 50 nm;

[0050] The carbon nanotubes (CNTs) are Nanocyl SA (Belgium), brand NC-7000, with an average diameter of 9.5 nm and an average length of 1.5 μm;

[0051] The expanded graphite (EG) is from Qingdao Yanhai Carbon Material Co., Ltd., YH-100, with a size of 100 mesh and an original expanded volume of 400-600 mL / g.

[0052] Example 1

[0053] This embodiment provides a polylactic acid composite material with a sandwich honeycomb structure and a preparation method thereof, the preparation method is as follows:

[0054] Step 1: Add 3.9 g CNT and 78 g cellulose nanofiber dispersion (CNFs, solid content of 2.5 wt%) to 1050 mL deionized water and stir for 1 h, then ultrasonicate in an ultrasonic cell crusher at a power of 600 W for 30 min to uniformly disperse the CNT in the aqueous solution (CNT / CNFs mass ratio is 2:1), which is used as the aqueous phase; then take 35 g PLA and fully dissolve it in 350 mL dichloromethane, which is used as the oil phase; pour 1050 mL of the aqueous phase into 350 mL of the oil phase, place the mixture in a homogenizer and homogenize and emulsify at 12000 rpm for 3 min to obtain a stable Pickering emulsion, then volatilize the homogenized and emulsified Pickering emulsion at room temperature for 24 h to obtain a PLA / 10CNT composite masterbatch, and dry it in a 60 ° C forced air oven for 12 h;

[0055] Step 2: Add 25g of PLA / 10CNT composite masterbatch and 25g of PLA powder into a Haake torque rheometer at the same time, melt blend at 180°C and 60rpm for 8min to obtain a diluted PLA / 5CNT composite, wherein the PLA / 5CNT composite particles include 5wt% carbon nanotubes; finally, the PLA / 5CNT composite is crushed in a high-speed crusher, sieved to obtain PLA / 5CNT composite particles with a particle size of 200 to 500μm, and dried in a 60°C forced air oven for 12h;

[0056] Step 3: After the PLA / 5CNT composite particles and the final content of 5% EG are mechanically blended in a high-speed mixer at 20000r / min for 2min, they are hot-pressed in a flat vulcanizer at 190°C and 10MPa to prepare a composite material PLA / 5CNT@5EG with an enhanced network structure, wherein the content of each component is shown in Table 1.

[0057] Table 1. Content of components in Examples 1 to 4

[0058]

[0059] Embodiments 2 to 4

[0060] Examples 2 to 4 respectively provide a polylactic acid composite material with a sandwich honeycomb structure and a preparation method thereof. Compared with Example 1, the final content of EG in step 3 is different, and the preparation method is the same. The content of each component of the composite material PLA / 5CNT@EG in Examples 2 to 4 is shown in Table 1.

[0061] Comparative Example 1

[0062] Comparative Example 1 provides a PLA / 5CNT composite particle. Compared with Example 1, Comparative Example 1 does not contain EG, and the specific preparation method is as follows:

[0063] Step 1: Add 3.9 g CNT and 78 g cellulose nanofiber dispersion (CNFs, solid content of 2.5 wt%) to 1050 mL deionized water and stir for 1 h, then ultrasonicate in an ultrasonic cell crusher at a power of 600 W for 30 min to uniformly disperse the CNT in the aqueous solution (CNT / CNFs mass ratio is 2:1), which is used as the aqueous phase; then take 35 g PLA and fully dissolve it in 350 mL dichloromethane, which is used as the oil phase; pour 1050 mL of the aqueous phase into 350 mL of the oil phase, place the mixture in a homogenizer and homogenize and emulsify at 12000 rpm for min to obtain a stable Pickering emulsion, then volatilize the homogenized and emulsified Pickering emulsion at room temperature for 24 h to obtain a PLA / 10CNT composite masterbatch, and dry it in a 60 ° C forced air oven for 12 h;

[0064] Step 2: Add 25g of PLA / 10CNT composite masterbatch and 25g of PLA powder into the Haake torque rheometer at the same time, melt blend at 180°C and 60rpm for 8min to obtain a diluted PLA / 5CNT composite, wherein the PLA / 5CNT composite particles include 5wt% carbon nanotubes; finally, the PLA / 5CNT composite is crushed in a high-speed crusher, sieved to obtain PLA / 5CNT composite particles with a particle size of 200 to 500μm, and dried in a 60°C forced air oven for 12h.

[0065] The contents of the components of the PLA / 5CNT composite particles are shown in Table 2.

[0066] Table 2. Component content of comparative example 1

[0067]

[0068] Comparative Example 2

[0069] Comparative Example 2 is pure PLA powder, which is mixed in a high-speed mixer at a speed of 20000 r / min for 2 min. Finally, it is hot-pressed in a flat vulcanizer at 190° C. and 10 MPa to obtain PLA material.

[0070] Comparative Examples 3 to 6

[0071] Comparative Examples 3 to 6 provide a PLA@EG composite material, respectively, and the specific preparation method includes: mechanically blending PLA powder and EG with different final contents in a high-speed mixer at 20000r / min for 2min, wherein the addition amount of expanded graphite is: 5wt%, 10wt%, 20wt% and 30wt% respectively; finally, hot pressing is performed in a flat vulcanizer at 190°C and 10MPa to obtain a PLA@xEG composite material, where x represents the mass fraction of EG. The details are as follows:

[0072] Comparative Example 3, PLA@5EG composite material, EG content 5wt%;

[0073] Comparative Example 4, PLA@10EG composite material, EG content 10wt%;

[0074] Comparative Example 5, PLA@20EG composite material, EG content 20wt%;

[0075] Comparative Example 6, PLA@30EG composite material, EG content 30wt%.

[0076] Comparative Example 7

[0077] Comparative Example 7 provides a DM-PLA / 5CNT / 30EG composite material prepared by a melt blending method. The specific preparation method includes: adding 47.5g PLA powder, 0.83g CNF, 1.67g CNT, and 21.4g EG to a Haake torque rheometer at the same time, the blending temperature is 180°C, the rotation speed is 60r / min, and the blending time is 8min, and then the blend obtained by melt blending is hot-pressed in a flat vulcanizer at 190°C and 10MPa to obtain a DM-PLA / 5CNT / 30EG composite material.

[0078] Comparative Example 8

[0079] Comparative Example 8 provides a DM-PLA / 5CNT@30EG composite material. Compared with Comparative Example 7, Comparative Example 8 uses mechanical blending to coat EG on DM-PLA / 5CNT particles. The specific preparation method is as follows:

[0080] Step 1: Add 47.5g PLA powder, 0.83g CNF and 1.67g CNT into the Haake torque rheometer at the same time, with the blending temperature at 180°C, the rotation speed at 60r / min and the blending time at 8min. Then, put them into a high-speed pulverizer for crushing, sieve to obtain DM-PLA / 5CNT particles with a particle size of 200-500μm, and dry them in a 60°C forced air oven for 12h.

[0081] Step 2: After mechanically blending the DM-PLA / 5CNT particles and EG with a final content of 30 wt% in a high-speed mixer at 20,000 r / min for 2 minutes, hot-pressing the mixture in a flat vulcanizer at 190°C and 10 MPa to prepare a DM-PLA / 5CNT@30EG composite material with a general network structure.

[0082] Example 5

[0083] Example 5 provides a polylactic acid composite material with a sandwich honeycomb structure and a preparation method thereof. Compared with Example 4, the difference in Example 5 is that in step 2, the PLA / 5CNT composite is crushed in a high-speed crusher and sieved to obtain PLA / 5CNT composite particles with a particle size of 50 to 200 μm, and the remaining operation steps are the same.

[0084] Example 6

[0085] Example 6 provides a polylactic acid composite material with a sandwich honeycomb structure and a preparation method thereof. Compared with Example 4, the difference in Example 6 is that in step 2, the PLA / 5CNT composite is crushed in a high-speed crusher and sieved to obtain PLA / 5CNT composite particles with a particle size of 500 to 900 μm, and the remaining operation steps are the same.

[0086] Example 7

[0087] Example 7 provides a polylactic acid composite material having a sandwich honeycomb structure and a preparation method thereof, wherein the preparation method is as follows:

[0088] Step 1: Add 3.9 g CNT and 65 g cellulose nanofiber dispersion (CNFs, solid content of 3 wt%) to 1050 mL deionized water and stir for 1 h, then ultrasonicate in an ultrasonic cell crusher at a power of 540 W for 1 h to uniformly disperse the CNT in the aqueous solution (CNT / CNFs mass ratio is 2:1), which is used as the aqueous phase; then take 42 g PLA and fully dissolve it in 350 mL dichloromethane, which is used as the oil phase; pour 1050 mL of the aqueous phase into 350 mL of the oil phase, place the mixture in a homogenizer and homogenize and emulsify at 12000 rpm for 3 min to obtain a stable Pickering emulsion, then volatilize the homogenized and emulsified Pickering emulsion at room temperature for 24 h to obtain a PLA / 8CNT composite masterbatch, and dry it in a 60 ° C forced air oven for 12 h;

[0089] Step 2: 15.5 g of PLA / 8CNT composite masterbatch and 34.5 g of PLA powder were added to a Haake torque rheometer at the same time, and melt-blended at 190° C. and 50 rpm for 10 min to obtain a diluted PLA / 2.5CNT composite, wherein the PLA / 2.5CNT composite particles include 2.5 wt% carbon nanotubes; finally, the PLA / 2.5CNT composite was crushed in a high-speed crusher, sieved to obtain PLA / 2.5CNT composite particles with a particle size of 200 to 500 μm, and dried in a 60° C. forced air oven for 12 h;

[0090] Step 3: After the PLA / 2.5CNT composite particles and EG with a final content of 30% are mechanically blended in a high-speed mixer at 20000r / min for 2min, they are hot-pressed in a flat vulcanizer at 190°C and 10MPa to prepare a composite material PLA / 2.5CNT@30EG with an enhanced network structure, wherein the content of each component is shown in Table 3.

[0091] Table 3. Component content of Example 7

[0092]

[0093]

Performance test

[0094] The conductivity of the composite materials prepared in Examples 1 to 4 and Comparative Example 1 was tested using a four-probe tester (RTS-8). The samples for the conductivity test were hot-pressed by a flat vulcanizer. The sample size was a disc with a diameter of 25 mm and a thickness of 1 mm. The results are shown in FIG. Figure 1 shown.

[0095] Depend on Figure 1It can be seen that the conductivity of the sandwich core formed by simple PLA / 5CNT composite particles is only 175.4S / m. However, the expanded graphite EG is coated on the surface of the PLA / 5CNT composite particles by mechanical blending, and the PLA / 5CNT@xEG composite material with an enhanced sandwich honeycomb structure is constructed by hot pressing. As the EG content increases, the conductivity of the composite material is greatly improved. When the EG content is 5wt%, the conductivity of the PLA / 5CNT@5EG composite material is 354.6S / m. As the EG content is further increased, when the EG content is 30wt%, the conductivity of the PLA / 5CNT@30EG composite material is 2924S / m. In summary, adding EG to the system and constructing an enhanced sandwich honeycomb structure greatly improves the conductivity of the PLA / 5CNT@xEG composite material.

[0096] The electromagnetic shielding performance of the composite materials prepared in Examples 1 to 4 and Comparative Example 1 was tested using a vector network analyzer (VNA, AV3672C) for characterization. The test sample size was 22.86×10.16×1.00 mm. The results are as follows: Figure 2 shown.

[0097] Depend on Figure 2 It can be seen that the conductivity of the sandwich core formed by simple PLA / 5CNT composite particles is only 22.5dB. However, the expanded graphite EG is coated on the surface of the PLA / 5CNT composite particles by mechanical blending, and the PLA / 5CNT@xEG composite material with an enhanced sandwich honeycomb structure is constructed by hot pressing. As the EG content increases, the electromagnetic shielding performance of the composite material is greatly improved. When the EG content is 5wt%, the electromagnetic shielding effectiveness value of the PLA / 5CNT@5EG composite material is 26.6dB. As the EG content is further increased, when the EG content is 30wt%, the electromagnetic shielding effectiveness value of the PLA / 5CNT@30EG composite material is 50.6dB. In summary, adding EG to the system and constructing an enhanced sandwich honeycomb structure greatly improves the electromagnetic shielding performance of the PLA / 5CNT@xEG composite material.

[0098] The thermal conductivity of the composite materials prepared in Examples 1 to 4 and Comparative Example 1 was tested. The samples for thermal conductivity test were hot-pressed by a flat vulcanizer. The sample size was a disc with a diameter of 25 mm and a thickness of 1 mm. The samples were characterized by a LFA467 laser thermal conductivity instrument. The results are as follows: Figure 3 shown.

[0099] Depend on Figure 3 It can be seen that the thermal conductivity of the sandwich core formed by pure PLA / 5CNT composite particles is only 0.4 W·m -1 ·K -1However, the expanded graphite EG was coated on the surface of PLA / 5CNT composite particles by mechanical blending, and the PLA / 5CNT@xEG composite material with enhanced sandwich honeycomb structure was constructed by hot pressing. With the increase of EG content, the thermal conductivity of the composite material was greatly improved. When the EG content was 5wt%, the electromagnetic shielding effectiveness value of the PLA / 5CNT@5EG composite material was 0.7W·m -1 ·K -1 As the EG content increases further, when the EG content is 30wt%, the electromagnetic shielding effectiveness value of the PLA / 5CNT@30EG composite material is 3.4W·m -1 ·K -1 In summary, adding EG to the system and constructing an enhanced sandwich honeycomb structure greatly improves the thermal conductivity of the PLA / 5CNT@xEG composite material.

[0100] The conductivity of the composite materials prepared in Examples 1 to 4 and Comparative Examples 2 to 6 was tested using a four-probe tester (RTS-8) and a high insulation resistance tester (ZC-36). The PLA material prepared in Comparative Example 2 had a conductivity lower than 10 -8 S / m, tested with a high insulation resistance tester, and other composite materials were tested with a four-probe tester. The samples for the conductivity test were hot-pressed by a flat vulcanizer. The sample size was a disc with a diameter of 25 mm and a thickness of 1 mm. The results are shown in the figure. Figure 4 shown.

[0101] Depend on Figure 4 It can be seen that the relationship between the conductivity of the PLA / 5CNT@xEG composite material with a sandwich honeycomb structure and the EG loading is as follows. With the increase of EG content, the conductivity of the composite material increases significantly. When the EG content reaches 30wt%, the conductivity of the PLA / 5CNT@30EG composite material is as high as 2924.0S / m, which is 725% higher than that of PLA / 5CNT@5EG (354.6S / m) and 1.3% higher than that of pure PLA in comparative example 2 (3.19×10 -14 S / m) increased by 17 orders of magnitude, showing excellent electrical conductivity. At the same time, the electrical conductivity of the comparative example 6PLA@30EG prepared by direct mechanical blending is only 188.7S / m. In summary, the construction of the sandwich honeycomb structure significantly improves the electrical conductivity of the composite material, achieving high electrical conductivity of the composite material.

[0102] The electromagnetic shielding performance of the composite materials prepared in Examples 1 to 4 and Comparative Examples 2 to 6 was tested using a vector network analyzer (VNA, AV3672C) for characterization. The test sample size was 22.86×10.16×1.00 mm. The results are as follows: Figure 5 shown.

[0103] Depend on Figure 5 It can be seen that the relationship between the electromagnetic shielding effectiveness value (EMI SE) of the PLA / 5CNT@xEG composite material with a sandwich honeycomb structure and the EG loading. As the EG content increases, the EMI SE value of the composite material continues to increase. When the EG content reaches 30wt%, under the condition that the sample thickness is only 1mm, the EMI SE value of the PLA / 5CNT@30EG composite material with a sandwich honeycomb structure reaches 50.6dB, which is 90% higher than PLA / 5CNT@5EG (26.6dB) and 2876% higher than the comparative example 2PLA (1.7dB), showing excellent electromagnetic shielding performance. At the same time, the EMI SE value of the comparative example 6PLA@30EG prepared by direct mechanical blending is only 20.6dB. In summary, it is shown that the construction of the sandwich honeycomb structure significantly improves the electromagnetic shielding performance of the composite material, realizes the high electromagnetic shielding of the composite material, and shows its application potential as an electromagnetic shielding material.

[0104] The thermal conductivity of the composite materials prepared in Examples 1 to 4 and Comparative Examples 2 to 6 was tested. The samples for thermal conductivity test were hot-pressed by a flat vulcanizer. The sample size was a round disc with a diameter of 25 mm and a thickness of 1 mm. The samples were characterized by a LFA467 laser thermal conductivity instrument. The results are as follows: Figure 6 shown.

[0105] Depend on Figure 6 It can be seen that the thermal conductivity of the two prepared composites increases steadily with the increase of EG content. When the EG content reaches 30wt%, the thermal conductivity of the PLA / 5CNT@30EG composite with a sandwich honeycomb structure reaches 3.4W·m -1 ·K -1 , is the thermal conductivity of pure PLA in Example 2 (0.2 W·m -1 ·K -1 ) is more than 15 times that of the thermal conductivity of 0.7 W·m -1 ·K -1 The PLA / 5CNT@5EG sample increased by 386%, and the composite material showed excellent thermal conductivity.

[0106] The composite materials prepared in Example 4 and Comparative Examples 7-8 were tested for conductivity. The samples for conductivity test were hot-pressed by a flat vulcanizer. The sample size was a disc with a diameter of 25 mm and a thickness of 1 mm. The samples were characterized using a four-probe tester (RTS-8). The test results are shown in FIG. Figure 7 shown.

[0107] Depend on Figure 7 It can be seen that compared with the comparative example 7 DM-PLA / 5CNT / 30EG and the comparative example 8 DM-PLA / 5CNT@30EG composite materials, the PLA / 5CNT@30EG composite material with a sandwich honeycomb structure prepared by combining the Pickering emulsion template method and the traditional melt blending method reached 2924.0S / m, showing the most excellent conductive performance, while the conductivity of the DM-PLA / 5CNT / 30EG composite material was only 1373.8S / m. This is because in the composite material prepared by melt blending, the filler is randomly dispersed, and a good connection cannot be formed between CNT and CNT, CNT and EG, and agglomeration is prone to occur, which leads to the poor effect of simple melt blending processing on building a good filling network. In addition, the electrical conductivity of the DM-PLA / 5CNT@30EG composite material is only 1528.0S / m, which is much smaller than that of PLA / 5CNT@30EG. This further demonstrates the advantage of constructing a sandwich honeycomb structure. It not only shows that filler dispersion is an important factor in improving the electrical conductivity of composite materials, but also shows that the secondary dispersion method plays a key role in improving the electrical conductivity of composite materials.

[0108] The composite materials prepared in Example 4 and Comparative Examples 7 to 8 were subjected to electromagnetic shielding performance tests. The samples for the electromagnetic shielding performance test were hot-pressed by a flat vulcanizer. The sample size was 22.86×10.16×1 mm. The samples were characterized using a vector network analyzer (VNA, AV3672C). The test results are shown in FIG. Figure 8 shown.

[0109] Depend on Figure 8 It can be seen that compared with the comparative example 7DM-PLA / 5CNT / 30EG and comparative example 8DM-PLA / 5CNT@30EG composite materials, the EMI SE value of the PLA / 5CNT@30EG composite material with a sandwich honeycomb structure reached 50.6dB, showing a more outstanding electromagnetic shielding performance. However, the EMI SE values ​​of the comparative example 7DM-PLA / 5CNT / 30EG composite material and the comparative example 8DM-PLA / 5CNT@30EG composite material were only 42.7dB and 39.2dB, respectively, which were significantly lower than the PLA / 5CNT@30EG composite material, which further reflects the advantages of constructing a sandwich honeycomb structure, and also shows that filler dispersion is an important factor in improving the electromagnetic shielding performance of composite materials, and the secondary dispersion method plays a key role in improving the electromagnetic shielding performance of composite materials.

[0110] The thermal conductivity of the composite materials prepared in Example 4 and Comparative Examples 7-8 was tested. The samples for the thermal conductivity test were hot-pressed by a flat vulcanizer. The sample size was a round disc with a diameter of 25 mm and a thickness of 1 mm. The samples were characterized by a LFA467 laser thermal conductivity instrument. The test results are shown in FIG. Fig. 9 shown.

[0111] Depend on Fig. 9 It can be seen that compared with the comparative example 7DM-PLA / 5CNT / 30EG and comparative example 8DM-PLA / 5CNT@30EG composite materials, the thermal conductivity of the PLA / 5CNT@30EG composite material with a sandwich honeycomb structure reached 3.4W·m -1 ·K -1 , showing the best thermal conductivity. However, the thermal conductivity of the DM-PLA / 5CNT / 30EG composite materials of Comparative Example 7 and Comparative Example 8 was only 1.2 W·m -1 ·K -1 and 1.8W·m -1 ·K -1 , which are significantly lower than PLA / 5CNT@30EG (3.4W·m -1 ·K -1 ), which further demonstrates the advantage of constructing a sandwich honeycomb structure. It also shows that filler dispersion is an important factor in improving the thermal conductivity of composite materials, and the secondary dispersion method plays a key role in improving the thermal conductivity of composite materials.

[0112] The cross-sectional morphology of the composite materials prepared in Example 4 and Comparative Examples 7-8 was observed. Fig.10 shown.

[0113] Depend on Fig.10It can be seen that while the honeycomb network structure is formed in the PLA / 5CNT@30EG composite material in Example 4, the wide isolation belt even has a large area of ​​connection and penetration between the isolation belts. At the same time, it can be clearly observed from the figure that at the interface connection between the sandwich and the honeycomb structure (the interface between EG and PLA / 5CNT), there is a phenomenon of mutual overlap and connection between the CNT in the PLA matrix and the tightly coated EG outside, which provides more conductive and thermal conductive paths for the transmission of electrons and phonons, which is also an important reason for the improvement of the electrical conductivity, electromagnetic shielding performance and thermal conductivity of the composite material. In summary, more conductive and thermal conductive paths are formed between the CNT connected in the sandwich core, the tightly coated EG outside, and the CNT and EG, so that the electrical conductivity and thermal conductivity of the PLA / 5CNT@30EG composite material are greatly improved. At the same time, the construction of the sandwich honeycomb structure will not only produce a large amount of reflections outside the composite material, but also produce multiple reflections and scattering inside the composite material, further increasing the consumption of electromagnetic waves inside the system, causing the electromagnetic shielding performance of the PLA / 5CNT@30EG composite material to be greatly improved. In the DM-PLA / 5CNT / 30EG composite material in Comparative Example 7, the fillers are randomly dispersed, and CNT and CNT, CNT and EG cannot form a good connection and obvious agglomeration occurs, which is the reason for its low electrical conductivity, electromagnetic shielding effectiveness value and thermal conductivity, and also shows that the simple melt blending process is not effective in building a good filling network. In addition, in the DM-PLA / 5CNT@30EG composite material in Comparative Example 8, the distribution of CNT in the sandwich prepared by direct melt blending is not uniform, and obvious agglomeration occurs, which is compared with the PLA / 5CNT@30EG composite material with a sandwich honeycomb structure having a sandwich core prepared by a secondary dispersion method, the electrical conductivity, electromagnetic shielding effectiveness value and thermal conductivity of the DM-PLA / 5CNT@30EG composite material are lower.

[0114] The conductivity test was carried out on the composite materials prepared in Example 4 and Examples 5-6. The samples for the conductivity test were hot-pressed by a flat vulcanizer. The sample size was a disc with a diameter of 25 mm and a thickness of 1 mm. The samples were characterized using a four-probe tester (RTS-8). The test results are shown in Table 4.

[0115] It can be seen from Table 4 that for Examples 5 to 6, PLA / 5CNT with a particle size of 50 to 200 μm is used as the PLA / 5CNT@30EG composite material with a sandwich core and PLA / 5CNT with a particle size of 500 to 900 μm is used as the sandwich core, respectively. The electrical conductivities of the composite materials are 2287.7 S / m and 2550.8 S / m, respectively, which are slightly lower than the PLA / 5CNT@30EG composite material with a particle size of 200 to 500 μm used as the sandwich core in Example 4 (2924.0 S / m). Therefore, PLA / 5CNT with a particle size of 200 to 500 μm is preferably used as the sandwich core to prepare a PLA / 5CNT@xEG composite material with a sandwich honeycomb structure.

[0116] The conductivity test was carried out on the composite materials prepared in Example 4 and Example 7. The samples for the conductivity test were hot-pressed by a flat vulcanizer. The sample size was a disc with a diameter of 25 mm and a thickness of 1 mm. The samples were characterized using a four-probe tester (RTS-8). The test results are shown in Table 4.

[0117] As shown in Table 4, PLA / 2.5CNT@30EG (Example 7) and PLA / 5CNT@30EG (Example 4) composite materials with different sandwich cores were prepared by mechanical blending, and the conductive properties of PLA / 5CNT@30EG and PLA / 2.5CNT@30EG composite materials were tested. Compared with the PLA / 2.5CNT@30EG composite material, the conductivity of the PLA / 5CNT@30EG composite material increased from 1274.7S / m to 2924.0S / m, which is a significant improvement, so the PLA / 5CNT composite particles are preferably used as the high-performance "sandwich" core.

[0118] The composite materials prepared in Example 4 and Example 7 were subjected to an electromagnetic shielding performance test. The samples for the electromagnetic shielding performance test were hot-pressed by a flat vulcanizer. The sample size was a sheet of 22.86×10.16×1 mm. The samples were characterized using a vector network analyzer (VNA, AV3672C). The test results are shown in Table 4.

[0119] As shown in Table 4, PLA / 2.5CNT@30EG (Example 7) and PLA / 5CNT@30EG (Example 4) composite materials with different sandwich cores were prepared by mechanical blending, and the electromagnetic shielding performance of PLA / 5CNT@30EG and PLA / 2.5CNT@30EG composite materials was tested. Compared with the PLA / 2.5CNT@30EG composite material, the electromagnetic shielding effectiveness value of the PLA / 5CNT@30EG composite material increased from 40.2dB to 50.6dB, which is a significant improvement, so the PLA / 5CNT composite particles are preferably used as the high-performance "sandwich" core.

[0120] The thermal conductivity of the composite materials prepared in Example 4 and Example 7 was tested. The samples for the thermal conductivity test were hot-pressed by a flat vulcanizer. The sample size was a disc with a diameter of 25 mm and a thickness of 1 mm. The samples were characterized using an LFA467 laser thermal conductivity meter. The test results are shown in Table 4.

[0121] As shown in Table 4, PLA / 2.5CNT@30EG (Example 7) and PLA / 5CNT@30EG (Example 4) composite materials with different sandwich cores were prepared by mechanical blending, and the thermal conductivity of PLA / 5CNT@30EG and PLA / 2.5CNT@30EG composite materials was tested. Compared with PLA / 2.5CNT@30EG composite materials, the thermal conductivity of PLA / 5CNT@30EG composite materials increased from 1.5 W·m -1 ·K -1 Increased to 3.4W·m -1 ·K -1 , which has a significant improvement, so PLA / 5CNT composite particles are preferably used as the high-performance "sandwich" core. Therefore, as a preferred embodiment, PLA / 5CNT composite masterbatch is used as the "sandwich" in the construction of the enhanced "sandwich honeycomb" structure.

[0122] The performance of the composite materials prepared in Examples 1 to 7 and Comparative Examples 1 to 11 was tested. The results are shown in Table 4.

[0123] Table 4. Performance test

[0124]

[0125] The embodiments described above are merely descriptions of preferred implementations of the present invention and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope of the present invention.

Claims

1. A polylactic acid composite material having a sandwich honeycomb structure, characterized in that: The composite material comprises a matrix and a filler, wherein the matrix is ​​polylactic acid, and the filler comprises carbon nanotubes, cellulose nanofibers, and expanded graphite. The composite material is prepared by the following method: dispersing carbon nanotubes in an aqueous solution as an aqueous phase under the action of a cellulose nanofiber dispersion, dissolving polylactic acid in dichloromethane as an oil phase, mixing the aqueous phase and the oil phase, homogenizing and emulsifying to obtain a Pickering emulsion, and obtaining a PLA / CNT composite masterbatch after the solvent evaporates; melt-blending the PLA / CNT composite masterbatch with polylactic acid, crushing and collecting to obtain PLA / xCNT composite particles; blending the PLA / xCNT composite particles with expanded graphite, and then hot-pressing to obtain a polylactic acid composite material PLA / xCNT@EG with a sandwich honeycomb structure; in the PLA / xCNT composite particles, x refers to the carbon nanotubes included in the PLA / xCNT composite particles in x wt%.

2. The polylactic acid composite material with a sandwich honeycomb structure according to claim 1, characterized in that: The composite material comprises 64.87-88.04 wt % of polylactic acid, 0.86-2.32 wt % of cellulose nanofibers, 1.72-4.64 wt % of carbon nanotubes, and 5-30 wt % of expanded graphite.

3. The polylactic acid composite material with a sandwich honeycomb structure according to claim 2, characterized in that: The PLA / xCNT composite particles include 2.5-5wt% carbon nanotubes.

4. The polylactic acid composite material with a sandwich honeycomb structure according to claim 1, characterized in that: The particle size of the PLA / xCNT composite particles is 50-900 μm.

5. The polylactic acid composite material with a sandwich honeycomb structure according to claim 4, characterized in that: The particle size of the PLA / xCNT composite particles is 200-500 μm.

6. The polylactic acid composite material with a sandwich honeycomb structure according to claim 2, characterized in that: In the PLA / CNT composite masterbatch, the mass ratio of carbon nanotubes to polylactic acid is 0.08-0.1:

1.

7. A method for preparing a polylactic acid composite material having a sandwich honeycomb structure according to any one of claims 2 to 6, characterized in that: The preparation method is as follows: Step 1: dispersing carbon nanotubes in an aqueous solution as a water phase under the action of a cellulose nanofiber dispersion, dissolving polylactic acid in dichloromethane as an oil phase, mixing the water phase and the oil phase, and homogenizing and emulsifying them to obtain a Pickering emulsion, and obtaining a PLA / CNT composite masterbatch after the solvent evaporates; Step 2: melt-blending the PLA / CNT composite masterbatch with polylactic acid, crushing and collecting to obtain PLA / xCNT composite particles; Step 3: The PLA / xCNT composite particles and expanded graphite are mixed and hot-pressed to obtain a polylactic acid composite material PLA / xCNT@EG with a sandwich honeycomb structure.

8. The method for preparing a polylactic acid composite material having a sandwich honeycomb structure according to claim 7, characterized in that: In step 1, the solid content of the cellulose nanofiber dispersion is 2.5-3wt%.

9. The method for preparing a polylactic acid composite material having a sandwich honeycomb structure according to claim 7, characterized in that: In step 1, the carbon nanotubes are uniformly dispersed in the aqueous solution after ultrasonication at a power of 540-600 W for 0.5-1 h in an ultrasonic cell crusher under the action of the cellulose nanofiber dispersion.

10. The method for preparing a polylactic acid composite material having a sandwich honeycomb structure according to claim 7, characterized in that: In step 2, the PLA / CNT composite masterbatch and polylactic acid are melt-blended in a Haake torque rheometer at 180-190° C. and 50-60 r / min for 8-10 min.

Citation Information

Patent Citations

  • Carbon nano tube (CNT) / polylactic acid (PLA) composite material and preparation method thereof

    CN102229743A

  • Preparation method of carbon nano tube (CNT) / polylactic acid (PLA) electromagnetic shielding composite material with isolation structure

    CN105038160A